POSSIBLE INFLUENCE OF LOXOPROFEN IN LIPOPOLYSACCHARIDE INDUCED ALTERATIONS IN SUCROSE INTAKE IN CHRONIC MILD STRESS MODEL IN MICE - S, KUNDU SMITA; G RANA, DIGVIJAYSINH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the present study was to evaluate the influence of Loxoprofen in sucrose intake in the absence and presence of Lipopolysaccharide in chronic mild stress model of depression in mice. Methods: There was a measurement of sucrose intake in chronic mild stress model (CMS), consisting of 21 days stress schedule in which mice were subjected to the treatment of Loxoprofen (16.8 mg/kg, p.o.) with or without treatment of lipopolysaccharide (LPS) (0.5 mg/kg i.p.) for the past 14 days. Results: The result of the present study indicated that mice treated with Venlafaxine and Loxoprofen showed a significant increase in the sucrose intake in stressed mice in chronic mild stress model. LPS-treated mice presented a decrease in sucrose intake when compared to controls. Similarly, Venlafaxine and Loxoprofen in the presence of LPS could increase the sucrose intake as compared to LPS treated stressed mice. Conclusion: The results of the present study showed that Loxoprofen could influence LPS induced alterations in sucrose intake in mice in chronic mild stress model. It can also indicate the possible anti-depressant effect of Loxoprofen in mice subjected to chronic mild stress model of depression, having its possible implication in future treatment of depression.